Hukum dan Kode Etik Profesi bagi Anggota Polri - Hamid, Moh. Renaldy; Moonti, Roy Marthen; Ahmad, Ibrahim; Kasim, Muslim A. (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyze the importance of professional laws and codes of ethics for members of the National Police of the Republic of Indonesia (Polri). The National Police professional code of ethics is a code of conduct that must be followed by every member of the National Police in carrying out their duties and responsibilities. This study examines the legal aspects that govern the code of ethics, as well as evaluating the challenges and its implementation in police practice. Data was collected through literature studies, analysis of laws and regulations, and in-depth interviews with members of the National Police. The results of the study show that effective enforcement of the code of ethics can strengthen integrity, professionalism, and public trust in the National Police. However, several challenges are still faced in the implementation of the code of ethics, such as the lack of socialization and strict supervision. This research provides recommendations to increase awareness and compliance of members of the National Police with the code of ethics, as well as strengthen its enforcement mechanism to strengthen.